Efektivitas Suplementasi Zink Dan Sinbiotik Dalam Mendukung Kesehatan Lansia: Tinjauan Sistematis - Rudy Hartono; Rusli Rusli; Aswita Amir; Agustian Ipa; Mira Andini; Hikmawati Mas’ud (Media Kesehatan Politeknik Kesehatan Makassar, 2025)
As the elderly population grows, life expectancy increases. This poses significant challenges to their health, particularly in maintaining immune and digestive function. Zinc and synbiotics (a combination of probiotics and prebiotics) are two promising nutritional interventions for supporting the health of the elderly. This article reviews the effects of zinc and synbiotics, as well as their combination, on elderly health, with a primary focus on immune response, sarcopenia, and fatigue. Based on a systematic review of literature from PubMed, Scopus, and Google Scholar, 600 articles were narrowed down to 10 selected articles (2017–2024) specifically involving randomized controlled trials, using the Cochrane Risk of Bias Tool and the PRISMA algorithm. The findings indicate that zinc supplementation has the potential to enhance the immune system and reduce inflammation, contributing to improved quality of life for the elderly. Meanwhile, synbiotics have been proven effective in improving gut health, addressing microbiota dysbiosis commonly found in the elderly, and enhancing gut microbiota balance that supports immune function. Zinc helps improve immune function and brain function, while synbiotics improve digestive health and reduce inflammation. When combined, both provide stronger and complementary effects in maintaining overall health in the elderly. Further research with stronger designs is needed to validate the benefits of both, and clinical recommendations for nutritional interventions in the elderly can be expanded based on these findings. Keywords: zinc, synbiotics, elderly, immune response